Sharīʿah Rulings in the Perspective of the Qur’an and the Sunnah: A Conceptual Examination of Taklīfī and Waḍʿī Legal Norms - Warsono Warsono; Siti Nurjanah; M. Lutfi Khakim; Nur Widiastuti (Journal of Social Science and Humanities, 2026)
This article examines the concept of hukum syara’ from the perspective of the Qur’an and the Sunnah as the primary normative foundations of Islamic law. The study focuses on the definition of hukum syara’, its epistemological position within Islamic legal thought, and its classification into hukum taklifi and hukum wadh’i. Using a qualitative library research method, this article analyzes classical and contemporary works on ushul fiqh and Islamic legal philosophy. The findings show that hukum syara’ is not merely a formal legal command but a divine discourse directed toward the conduct of mukallaf through demands, prohibitions, choices, and legal determinations. Hukum taklifi includes wajib, mandub, haram, makruh, and mubah, while hukum wadh’i includes sabab, syarat, and mani’. These two classifications demonstrate that Islamic law contains both normative obligations and operational legal mechanisms. The article argues that a systematic understanding of hukum syara’ is essential for strengthening Islamic legal studies because it clarifies the relationship between revelation, legal reasoning, and practical human conduct.